For excellence in Cuban dental publications - Alain Manuel Chaple Gil; Josefa Dolores Miranda Tarragó (Editorial Ciencias Médicas, 2019)
The publications on Stomatology, in Cuba, appear in many magazines of the national territory, foreign and not precisely specialized in the subject. Researchers of the stomatological union have given themselves the task of showing the world their achievements through scientific publication. But, it is the responsibility of each disseminating entity to show the transparency with which the editorial process is carried out and to require the authors to demonstrate the same characteristics with their research. Hence the existence of editorial policies and standards for authors, which each magazine in particular has the responsibility to review and systematize according to current times. In September 2018, the SciELO Network Meeting was held in Sao Paulo, Brazil where, among other topics, the communication of research through open science, the transparency of processes and the opening of contents with a view were discussed. to promote the reusability and replicability of the methods. These precepts and others motivated the aforementioned network to modify its editorial and indexing policies for the journals that comprise it. The Cuban Journal of Stomatology joins the group of journals that welcome the new policies of the SciELO network and intend that their authors show their research with the excellence we advocate for this new year 2019. The new rules for authors are available in the Journal's Open Journal System (OJS) in Spanish and English and among other updates they reflect the modality of "Letter to the Editor", section of the magazine that was needed to be able to give participation to the readers and authors interested in offering opinions and comments about our publication. The challenge now takes us to the systematic, effort and learning of everything that can be done in order to achieve that the Cuban Stomatology has a disseminator of excellent research.